Molecular Phylogeny and Taxonomy of the Genus Minidiscus (Bacillariophyceae), with Description of Mediolabrus gen. nov. Issue 6 (20th July 2020) - Li, Yang; Guo, Xiao‐Hui; Lundholm, Nina
Abstract : The genus Minidiscus comprises a group of ecologically‐important and globally‐distributed planktonic diatoms that are characterized by their small cell size, high mantle and processes more or less concentrated in the valve center. Monoclonal strains were established from collections along the Chinese coast. In the phylogenetic analyses inferred from a LSU and SSU dataset, six Minidiscus species clustered into two well‐supported clades. The first clade was located within a larger clade formed mainly by Thalassiosira taxa, and the second clade appeared as sister to a clade comprising the genus Skeletonema . Hence, presently known Minidiscus do not form a monophyletic clade, but rather make up a phenotypic grouping. Based on the morphology of the type species, M. trioculatus, as well as morphological characters of all taxa in the clade with M. trioculatus, Minidiscus is characterized by having fultoportula(e) in the valve center or sub‐centered close to a single rimoportula, and the cells are usually cylindrical. Mediolabrus gen. nov. is proposed to accommodate species in the second clade. The main difference between Minidiscus and Mediolabrus is the type of process found in the valve (sub‐)center, with fultoportula(e) close to a rimoportula in the former, and only a single rimoportula in the latter. According to the above criteria, previously described Minidiscus taxa were re‐examined, and either retained in Minidiscus or transferred to Mediolabrus .